‘Paul Biya fait dire qu’il est vivant’: histoire médiatique d’un revenant - Valentina Tarquini (MediAzioni)
This research analyses the circulation of a rumour in Cameroonian media, namely the fake news about the death of Paul Biya, the President of the Republic of Cameroon, who did not appear publicly at the start of the Covid19 pandemic, casting doubt on his state of health. We propose to use the biological model of virality to interpret the rumour as an expression of the immunity of the ‘social body’ that resists the ‘political body’, which has enjoyed absolute immunity since 2008. The Head of State is heavily criticised, among other things, for the armed repression that has been going on since 2017 in the country’s English-speaking minority territories. Therefore, this rumour seems to be paving the way for the visibility of an event unknown to international public opinion. While the spreaders of the rumour use enunciative erasure to protect themselves, the Head of State pursues his ‘strategy of silence’ by expressing himself by proxy.